Youth Participation in Public Legal Awareness: The Case of Mass Vaccination for COVID-19 in Indonesia - Wati, Elvita Anggoro; Pratama, Muhammad Aldiansyah; Andrian, Nazella Jeanny (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
The Corona Virus Disease 2019 (COVID-19) pandemic has put new challenges for all countries, especially Indonesia. Tireless efforts have been made to mitigate the number of spread of the COVID-19 virus, such as by implementing physical distancing, washing hands regularly, and wearing masks in public area. In the other side, the government seeks to provide protection to the community through vaccination programs. The COVID-19 vaccination is expected to protect people by creating an antibody (immune system) and preventing transmission of virus among people. The effectiveness of this vaccination is supported by the issuance of Presidential Decree No. 14 of 2021 as one of the government methods for the procurement and implementation of mass vaccinations in Indonesia. It is expected to have a significant impact on the fight against the pandemic. However, the regulation has not been properly implemented because there are still many negative assumptions that vaccine has dangerous side effects. Therefore, many people are reluctant to be vaccinated. The study used a normative legal research, and the data was taken from secondary data with statutory, analytical, and legal conceptual approaches. The results showed that youth participation was needed to support the government in realizing mass vaccination for the community, by going directly to the community to conduct dissemination to increase awareness in the community on the importance of the vaccine.